The Translation of Indonesian Expressions into English in the Novel the Architecture of Love by Ika Natassa - Vista Citra Puspita Swari; Baharuddin Baharuddin; Lalu Jaswadi Putera; Lalu Thohir (Journal of English Education Forum (JEEF), 2026)
Literary translation requires translators to convey not only linguistic meaning but also the cultural nuances and stylistic features embedded in the source text. This study aimed to analyze the translation techniques used in translating Indonesian expressions into English in the bilingual novel The Architecture of Love by Ika Natassa and to identify the dominant technique employed. A descriptive qualitative research design was adopted. The data consisted of 74 Indonesian expressions selected from eight chapters of the novel. Data were collected through documentary analysis and analyzed using the qualitative data analysis procedures proposed by Miles and Huberman, with the analysis guided by the translation theories of Newmark, Baker, and Hurtado Albir. The findings revealed that the translator employed three main translation techniques: modulation, adaptation, and equivalence. Modulation was the most dominant technique, occurring in 37 cases (50%), followed by equivalence with 19 cases (25.7%) and adaptation with 18 cases (24.3%). The predominance of modulation indicates that the translator frequently modified perspectives, sentence structures, and figurative expressions to produce natural, fluent, and culturally acceptable translations for English readers. Adaptation was mainly used to translate culture-specific expressions, whereas equivalence was applied when established English counterparts existed. These findings demonstrate that effective literary translation requires flexibility in balancing semantic accuracy, cultural transfer, and readability while preserving the meaning and aesthetic qualities of the original text.